Motivation In Choosing Coffee Picking Methods - Timbul Rasoki (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to understand the motivations of coffee farmers, specifically those practicing the "petik pelangi" method, in Bukit Sari Village, Kabawetan District, Kepahiang Regency, Bengkulu Province. Methodology: The research employed a Likert scale method, sampling 35 respondents. Factors such as age, education level, and experience were analyzed to determine their impact on farmers' motivations. Results: The study found that internal factors such as age (34-59 years), education level (mostly higher education), and experience significantly influence farmers' motivation. Additionally, land ownership size and family dependents also affect motivation. Findings: Internal factors had a slightly higher average motivation score (17.6) compared to external factors (17.46). The price difference between "petik merah" and "petik pelangi" coffee reflects complex market dynamics. Despite the higher price of "petik merah" coffee, many farmers and the community prefer the "petik pelangi" method due to the motivation to harvest coffee when it is still colorful. Novelty: This research provides new insights into the motivations behind the "petik pelangi" coffee harvesting method, highlighting the factors that influence farmers' choices. Originality: The study offers an in-depth understanding of the internal and external factors affecting coffee farmers' motivations, with a focus on a unique harvesting method that is less commonly studied. Conclusions: Internal factors such as age, education level, and experience are significant motivators for coffee farmers practicing the "petik pelangi" method. Despite the higher market value of "petik merah" coffee, the colorful harvest method remains popular due to intrinsic motivations. Paper Type: Empirical Research Article Keywords: Harvesting method; Motivation; Coffee